The relationship between English self-efficacy and TOEFL scores of university students - Hikmah, Darul; Daniel, Luca (Early Publishing Group, 2025)
This study investigates the relationship between English self-efficacy and TOEFL scores among university students, emphasizing the importance of psychological factors in language assessment performance. As English proficiency becomes increasingly vital for academic and professional opportunities globally, understanding the psychological determinants of language test outcomes is crucial. While prior research has examined specific language skills or general academic self-efficacy, limited studies have explored the holistic role of overall English self-efficacy in predicting performance on standardized tests like the TOEFL within university settings. This research aims to fill this gap by analyzing how students’ confidence in their English abilities influences their test results and whether self-efficacy serves as a significant predictor of TOEFL performance. Employing a correlational research design, the study involved 94 undergraduate students from various faculties at an Indonesian university. Data collection included administering a validated English Self-Efficacy Questionnaire and retrieving institutional TOEFL scores from the university database. Participants volunteered and provided informed consent, ensuring ethical compliance. Data analysis involved descriptive statistics, correlation analysis, and multiple regression procedures to examine the predictive relationship between self-efficacy and TOEFL scores. The key findings indicate a significant positive correlation between English self-efficacy and TOEFL performance, with self-efficacy emerging as a meaningful predictor of test scores. Students with higher confidence in their English skills tend to achieve better results, demonstrating the psychological influence on language assessment outcomes. These results underscore the importance of fostering positive self-beliefs in learners to enhance both motivation and performance in high-stakes testing environments. The study's implications suggest that language instruction should integrate strategies to boost learners' self-efficacy, thereby contributing to improved academic achievement and more effective language assessment practices. This research offers valuable insights for educators and policymakers aiming to support optimal language learning and testing success.